"When are you getting married?" : An exploration of Singaporeans' milestones while progressing into marriage - Mak, Cheng Hon (2019)
Delaying marriage has serious repercussions for Singapore’s population demographic resulting from the strong association between marriage and fertility. Using a life course approach which emphasises on the linkages between independent events, this paper investigates 2 things. Firstly, the reasons for delayed marriages amongst Singaporeans through understanding the normative events, associated cultural timings and actual Singaporeans' intended progression towards marriage. Secondly, how normative expectations and individual agency interact to produce the Singaporean life course towards marriage. Based on interview results gathered from 10 respondents, this paper concludes that there exist durational and sequential expectations on 10 culturally established milestones. They are - singlehood, dating, completing education, employment, economic stability, proposal, cohabitation, marriage, acquiring a house and childbirth. By acknowledging both the normative and agency aspects of the life course, this paper discusses how individuals act freely within the bounds of normative standards when making decisions relating to marriage.